Electronic Textbooks Advantages and Challenges for the Hellenic Higher Education and Publishing Community. Issue 6 (19th August 2014) - KOUIS, DIMITRIOS; Konstantinou, Nikolaos
Abstract : Purpose: In the higher education domain, the shift to electronic textbook adoption entails numerous benefits. However, reluctance is noted by the students as well as by the publishers, impeding the faster realization of this change. Decision makers (such as Ministry of Education and Universities Administrations) need actual survey data in order to plan and perform the best strategy plan for the transition to the e-textbook era. Design/methodology/approach: Two different surveys took place among higher education students and academic textbook publishers in Greece. More specifically, the purpose of these surveys was twofold: First, to identify both students and local publishers' views towards the e-textbooks as the near future successor of printed books. Second, the results of the in-depth study will enable propose certain solutions for the Hellenic higher education textbook system, which has reached an economic and functional deadlock. Our findings will easily adopted by other, similar educational system across Europe as well. Findings: Our findings reflect a situation where e-textbooks will replace the printed, but not in the near future as both technology providers and publishers have to overcome many technical obstacles. Students are expecting the transition to occur soon, but still remain very reluctant about the inconvenience might caused to their reading habits. Originality/value: The results are unique and in alignment with similar surveys in other educational systems.